A roadmap for the functional annotation of protein families: a community perspective. (12th August 2022) - de Crécy-lagard, Valérie; Amorin de Hegedus, Rocio; Arighi, Cecilia; Babor, Jill; Bateman, Alex; Blaby, Ian; Blaby-Haas, Crysten; Bridge, Alan J; Burley, Stephen K; Cleveland, Stacey; Colwell, Lucy J; Conesa, Ana; et al.
Abstract: Over the last 25 years, biology has entered the genomic era and is becoming a science of 'big data'. Most interpretations of genomic analyses rely on accurate functional annotations of the proteins encoded by more than 500 000 genomes sequenced to date. By different estimates, only half the predicted sequenced proteins carry an accurate functional annotation, and this percentage varies drastically between different organismal lineages. Such a large gap in knowledge hampers all aspects of biological enterprise and, thereby, is standing in the way of genomic biology reaching its full potential. A brainstorming meeting to address this issue funded by the National Science Foundation was held during 3–4 February 2022. Bringing together data scientists, biocurators, computational biologists and experimentalists within the same venue allowed for a comprehensive assessment of the current state of functional annotations of protein families. Further, major issues that were obstructing the field were identified and discussed, which ultimately allowed for the proposal of solutions on how to move forward.